Kemampuan Kewirausahaan Petani Muda Hortikultura di Provinsi Jawa Barat - Mukti, Gema Wibawa; Charina, Anne; Kusumo, Rani Andriani Budi (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Currently, more than 65% of Indonesian farmers are 45 years old and above, and it is estimated that in the next 30 years, Indonesia will experience a shortage of farmers. This trend is worrying, as the aging of the agricultural workforce and the lack of young farmers pose significant challenges to the future sustainability of the agricultural sector in Indonesia. In facing these challenges, the government needs to cultivate a younger generation of farmers who are relatively well-educated and highly creative. This study aims to gain a deeper understanding of the key entrepreneurial competencies possessed by young farmers. This study uses quantitative methods with a survey approach, the variables studied include the entrepreneurial ability of young farmers, and how the relationship between the profile of young horticultural farmers and their entrepreneurial abilities. The number of horticultural young farmer respondents taken in this study was 100 people. The results showed that education proved to have a positive and significant relationship with entrepreneurial ability, while farming experience showed a negative relationship. Entrepreneurship development programs for young farmers should concentrate on improving education, skills, and experience, as well as creating a more conducive ecosystem to encourage entrepreneurial interest among youth in the sector. This study shows that there is a need to motivate young farmers to improve their entrepreneurial capabilities and increase their interest in various entrepreneurial activities.